Relación entre el sistema de control interno y la gestión financiera de las organizaciones no gubernamentales del departamento de Loreto, durante el periodo 2021 - Honorio Vasquez, Felix Jesus (2023)
As for the department of Loreto, there are many NGOs, since this department is one of the poorest in the country, with large gaps in infrastructure, education, health, etc. In addition, it has a strategic position for the environmental conservation of Peru and the world, therefore, many NGOs focus their attention on working in this department to promote sustainable development, in this sense, the objective of the research is to determine the relationship between internal control and financial management of NGOs in the department of Loreto, during the 2021 period, for this, this work uses a quantitative, non-experimental, and correlational design methodology; in which we find that when applying our Spearman correlation model, it is shown that there is a positive correlation between internal control and financial management of NGOs in the department of Loreto, during the 2021 period, and this relationship or correlation is 87%. , indicating that if the efficiency of internal control processes increases, the efficiency of financial management will also increase significantly and in a proportion of 87%.